Understanding How Export Stimuli, Export Knowledge, Product Standards, and Marketing Strategies Shape the Export Performance of Indonesian MSMEs - Sekar Tri Widati; Suparno; Saparuddin Mukhtar (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study examines how export stimuli, export knowledge, product standards, and marketing strategies shape the export performance of Indonesian MSMEs. Using a qualitative approach, semi-structured interviews with 12 MSME owners and managers were thematically analyzed. Findings reveal that unsolicited buyer inquiries and government-led trade missions often trigger market entry, while regulatory knowledge and cultural awareness sustain operations. The significance of this study lies in its dual contribution. Practically, it provides actionable insights for MSME owners, trade associations, and policymakers to design more effective export promotion policies that integrate market access with continuous capacity building. Academically, it advances business and economic studies by offering a qualitative, context-specific understanding of how internal capabilities and external factors interact to influence MSME export performance, a perspective often overlooked in quantitative research.